2005
DOI: 10.1542/peds.2004-2764
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Study of Irritable Bowel Syndrome in Adolescents and Children in China: A School-Based Study

Abstract: ABSTRACT. Objectives. To explore the prevalence of irritable bowel syndrome (IBS) and its distribution characteristics of adolescents and children in China and its contributing factors.Methods. This study was a stratified, randomized study by clustering samples, which involved 5403 students whose age range was 6 to 18 years from 9 schools, and was conducted in Heilongjiang Province and Shanghai. All students studied were requested to fill in a questionnaire. IBS was diagnosed according to Rome II criteria.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
85
4
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 13 publications
5
85
4
4
Order By: Relevance
“…9,10,14,15 We found the prevalence of IBS among high school students to be 6.0%. This finding was lower than the 11.44-17.35% among Chinese adolescents aged 13-17 years using the Rome II criteria.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…9,10,14,15 We found the prevalence of IBS among high school students to be 6.0%. This finding was lower than the 11.44-17.35% among Chinese adolescents aged 13-17 years using the Rome II criteria.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, Liu Dong et al did not find a relationship between the stress of school work and parents' disciplinary forms to IBS. 14 Park et al also found no significant relationship between examination-related stress and IBS. 3 However, the higher prevalence among students with IBS who experienced stress by scolding and corporal punishment were reported by other previous studies.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations